2018
DOI: 10.1177/1526602818808296
|View full text |Cite
|
Sign up to set email alerts
|

Anatomical Predictors of Endoleaks or Migration After Endovascular Aneurysm Sealing

Abstract: To identify preoperative anatomical aortic characteristics that predict seal failures after endovascular aneurysm sealing (EVAS) and compare the incidence of events experienced by patients treated within vs outside the instructions for use (IFU). Methods: Of 355 patients treated with the Nellix EndoVascular Aneurysm Sealing System (generation 3SQ+) at 3 high-volume centers from March 2013 to December 2015, 94 patients were excluded, leaving 261 patients (mean age 76±8 years; 229 men) for regression analysis. O… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
16
0

Year Published

2018
2018
2021
2021

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 12 publications
(16 citation statements)
references
References 19 publications
0
16
0
Order By: Relevance
“…Further data from United Kingdom and Europe supported these findings. 20,21 In light of this and in consultation with the Medicines and Healthcare Products Regulation Agency, Nellix was withdrawn from the UK market.…”
mentioning
confidence: 99%
“…Further data from United Kingdom and Europe supported these findings. 20,21 In light of this and in consultation with the Medicines and Healthcare Products Regulation Agency, Nellix was withdrawn from the UK market.…”
mentioning
confidence: 99%
“…26 However, the proximal displacement rate in this group was still 30% despite adherence to the new IFU. van Noort et al 27 recently reported a 28% rate of events (migration >5 mm, any endoleak, and/or aneurysm growth >5 mm) in their 46-patient subgroup complying with the IFU-2016. These results should encourage clinicians to pursue close surveillance even in patients treated within the IFU for early detection of proximal displacement and AAA growth.…”
Section: Discussionmentioning
confidence: 98%
“…The first publications describing EVAS safety and efficacy showed adequate outcomes 11,34,35 ; however, long-term device limitations, migration, and sac remodeling have to be studied more closely to prove whether this technique is a feasible and effective approach. 36,37…”
Section: Discussionmentioning
confidence: 99%